Development of Isiolo County rangeland management bill regulation - International Livestock Research Institute (International Livestock Research Institute, 2024)
The County Government of Isiolo through lead department of livestock development has been developing Isiolo county rangeland management bill since August 2022 in collaboration with World food programme (WFP), Mid-P, Northern Rangeland Trust (NRT), AMAYA Triangle, NAWIRI, ILRI, Veterinary San Frontiers (VSF-Suisse), Kenya Rapid, Listen Project among other. The partners have supported the initiative technically and financially. The overall objective of the bill is to provide legal framework for management, conservation and utilization of the rangeland resources. The specific object of the bill is to facilitate and promote the sustainable and holistic management of rangelands and rangelands resources through: (a) strengthening customary mechanisms for grazing control; (b) facilitating community peace building ; (c) promoting inter-community access to rangelands resources; (d) regulation of fencing in rangelands areas; (e) Protection of seasonal rangelands reserves; (f) optimize the economic potential of the rangelands; (g) facilitate land related County Planning and Development under the Fourth Schedule of the Constitution of Kenya; and (h) adopt any other approaches and initiatives in furtherance of the objectives stated above.